Upregulation of miR-183 inhibits the invasion and migration of endometrial stromal cells in endometriosis patients by downregulating Ezrin - Shi, Jinmei; Cai, Junbo; Kong, Lin; Ying, Lingxiao; Liu, Xing; Jiang, Mengting; Pan, Dan (Frontiers in Oncology, 2025)
PurposeThe present study investigated the expression and role of miR-183 in the proliferation, invasion, migration, and apoptosis of endometrial stromal cells in endometriosis patients and the potential involvement of targeting Ezrin.MethodsNormal, non-ectopic, and ectopic endometrial stromal cells (ESCs) were extracted from endometrial samples. RT-qPCR was used to evaluate miR-183 expression levels in endometrial tissue samples. Flow cytometry, cell proliferation assay, adhesion assay and Transwell assays and cell scratch assay were performed to assess cell apoptosis, viability, migration, and invasion of cells transfected with miR-183 inhibitor, miR-183 mimics, or controls. Western blotting was used to determine the expression of the migration-and invasion-related proteins. The expression status of RhoA/ROCK/Ezrin in endometriosis was verified by animal models.ResultsmiR-183 expression levels were markedly downregulated and RhoA and Ezrin expression levels were upregulated in ectopic endometrial samples. Upregulation of miR-183 expression inhibited cell apoptosis, migration and invasion and promoted cell adhesion in ESCs, but had no significant impact on cell proliferation. miR-183 mimics decreased the expressions of Ezrin, RhoA, RhoC, and Rock.ConclusionUpregulated expression of miR-183 promoted cell adhesion and suppressed the apoptosis, invasion, and migration of ESCs by downregulating Ezrin. miR-183 may play a suppressor role in endometriosis by downregulating Ezrin to inactivate the Rho/ROCK pathway.